HUBUNGAN WAKTU TUNGGU HASIL LABORATORIUM DENGAN KEPUASAN PASIEN POLI RAWAT JALAN DI RUMAH SAKIT BAKTI TIMAH - Rakhman, Fikri (JURNAL SMART ANKes, 2025)
Waiting time for laboratory examination is one of the indicators most often used as an indicator of service performance in the laboratory. In addition, clinicians use examination waiting time as an indicator to assess the quality of a laboratory. The purpose of this research is to explain and prove the relationship between waiting time for laboratory results and outpatient polyclinic patient satisfaction at Bakti Timah Hospital Pangkalpinang in 2022. The design of this research is quantitative research with the type of research used is associative, the research was conducted from December 2022 to February 2023 on 304 respondents. Inclusion criteria for patients carrying out types of laboratory service examinations consist of: Creatinine, Ureum, Hbs Ag, Sodium, Potassium, Cloride and Anti HIV which has an estimated standard inspection time of 120 minutes. The data obtained were analyzed using univariate, bivariate and multivariate analysis. The results of the bivariate test showed a relationship between age, gender, education, and occupation and waiting time for laboratory test results at Bakti Timah Hospital Pangkalpinang. In addition, there is a significant relationship between age, gender, education, occupation and waiting time for laboratory test results with patient satisfaction at Bakti Timah Hospital Pangkalpinang. From the results of multivariate analysis it turns out that the variables have a significant relationship with satisfaction in laboratory patients and outpatient polyclinics at Bakti Timah Hospital Pangkalpinang it is only the variable length of waiting time for laboratory examinations that influences the satisfaction of laboratory patients and outpatient polyclinics at Pangkalpinang Hospital, because it has a significant value / p-value of 0.000 (<0.05). With a constant negative value of -4,860 which means that the lower the waiting time will increase patient satisfaction. While the patient characteristic variables, namely age, gender, education, and occupation as confounding variables, do not have a significant relationship with satisfaction in laboratory patients and outpatient polyclinics at Bakti Timah Hospital Pangkalpinang.